Peningkatan Usaha Peternakan Itik Petelur Lokal dengan Pakan Suplementasi Maggot Black Solder Fly di Desa Ringinanyar, Kecamatan Ponggok, Kabupaten Blitar - Sayyidina Hamzah; Sumiati Sumiati; Prayoga Suryadarma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Ringinanyar is one of the duck center in Blitar. Duck farm at Ringinanyar Village were still reared by intensive system management. Farmers still do not understand about laying duck feed. Due to poor knowladge of feedstuff, farmers were not able to control egg’s price then lead farmer dependency on middleman. Maggot suplementation on feed has a concept on optimizing utilization of local feedstuff. In order to increase egg production. Program’s partner of Stasium Lapang Agro Kreatif (SLAK) is Kelompok Ternak Maju at Desa Ringinanyar, Kecamatan Ponggok, Kabupaten Blitar. The program was held on November 2019 to Januari 2019. The program was started by socialization about program information, then continue by training on maggot-suplemented feed, the farmers were expected to be indipendence on fullfilled their own feed demand then improving their own wealth. The programs were done as it as were expected and maggot-suplemented feed production would be regulary done by the farmers.